2022
DOI: 10.1039/d2tb00397j
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the visible-light-driven photocatalytic antibacterial performance of MoS2 nanosheets by poly(3-(4-methyl-3′-thiophenoxy))propyltrimethylammonium chloride (PThM) modification

Abstract: A schematic diagram of the synthesis of PTh/MoS2 and PThM/MoS2 and their use in the inactivation of E. coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…38 The surface charge of MoS 2 nanosheets was also detected, and its value was −28.5 eV (Figure S1), which was similar to previous research results. 25,35 The negative charge of MoS 2 nanosheets caused by the sulfur atom in the nanosheets made it easier to absorb Ag + through the electrostatic reaction, contributing to the synthesis of Ag@MoS 2 nanosheets. The SEM images (Figure 1D) indicated that Ag-Pd nanoparticles marked by red circles were successfully embedded between the sheets of MoS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The surface charge of MoS 2 nanosheets was also detected, and its value was −28.5 eV (Figure S1), which was similar to previous research results. 25,35 The negative charge of MoS 2 nanosheets caused by the sulfur atom in the nanosheets made it easier to absorb Ag + through the electrostatic reaction, contributing to the synthesis of Ag@MoS 2 nanosheets. The SEM images (Figure 1D) indicated that Ag-Pd nanoparticles marked by red circles were successfully embedded between the sheets of MoS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…22−24 However, the surface electronegativity and easy accumulation of pure MoS 2 nanomaterials reduce the contact between bacteria and MoS 2 , thus further decreasing the sterilization efficiency. 25,35 Nanozymes are considered as a promising and efficient spectral antibacterial agent, mainly because they can spontaneously generate reactive oxygen species (ROS, such as such as 1 O 2 , • OH, etc.) in situ to inactivate bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced photocatalytic performance is attributed to the facilitated charge separation and increased amounts of ROS. 59 Cai fabricated a coating of MoS 2 /PDA–arginine–glycine–aspartic acid (RGD). 60 The coating on the Ti implant not only enhanced osteogenesis but also exhibited effective antibacterial performance.…”
Section: Sulfidesmentioning
confidence: 99%
“…Therefore, using nanomaterials as antibacterial agents was a very effective way to solve the problem of insufficient antibacterial materials. Commonly used antimicrobial nanomaterials include carbon-based materials, 3,10−13 metal nanoparticles, [14][15][16][17][18]25,26 metal oxides/sulfides, 1,19−22 and functional polymers. 23−26 had significant development in biology due to their excellent antibacterial ability and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%